2010
DOI: 10.1029/2009jd013601
|View full text |Cite
|
Sign up to set email alerts
|

Biomass burning smoke aerosol properties measured during Fire Laboratory at Missoula Experiments (FLAME)

Abstract: [1] During the Fire Laboratory at Missoula Experiments (FLAME), we studied the physical, chemical, and optical properties of biomass burning smoke from the laboratory combustion of various wildland fuels. A good understanding of these properties is important in determining the radiative effects of biomass burning aerosols, with impacts on both local and regional visibility and global climate. We measured aerosol size distributions with two instruments: a differential mobility particle sizer (DMPS) and an optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
206
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(227 citation statements)
references
References 81 publications
(94 reference statements)
20
206
1
Order By: Relevance
“…Therefore, the larger AAE BC obtained at the rural site could be a result of the smaller BC diameters of biomass burning in PRD. It should be noted that previous studies showed that AAE of ambient aerosol can also be influenced by a couple of other factors, such as size distribution, mixing state, and fractal dimension of BC particles (Levin et al, 2010;Gyawali et al, 2009;Scarnato et al, 2013;Bond and Bergstrom, 2006), but it is quite complicated and almost impossible to consider the influence of all these factors simultaneously. Scarnato et al (2013) also pointed out that it is very difficult to clarify the relationship between AAE and aerosol morphology and mixing state due to quite complicated mechanisms in real cases.…”
Section: Determination Of the Aae For "Pure" Bc Aerosolmentioning
confidence: 99%
“…Therefore, the larger AAE BC obtained at the rural site could be a result of the smaller BC diameters of biomass burning in PRD. It should be noted that previous studies showed that AAE of ambient aerosol can also be influenced by a couple of other factors, such as size distribution, mixing state, and fractal dimension of BC particles (Levin et al, 2010;Gyawali et al, 2009;Scarnato et al, 2013;Bond and Bergstrom, 2006), but it is quite complicated and almost impossible to consider the influence of all these factors simultaneously. Scarnato et al (2013) also pointed out that it is very difficult to clarify the relationship between AAE and aerosol morphology and mixing state due to quite complicated mechanisms in real cases.…”
Section: Determination Of the Aae For "Pure" Bc Aerosolmentioning
confidence: 99%
“…Therefore, a seasonal shift towards larger particles in summertime could account for some of the model-measurement discrepancy. However, measurements of the geometric mean diameters for ambient SOAdominated aerosol and fresh smoke are similar (Levin et al, 2009(Levin et al, , 2010. Additionally, the fraction of total AOD accounted for by organics in the model is on average less than 15 % in the summertime, and substantial seasonal changes in the size of inorganic aerosol are less likely (e.g., Stanier et al, 2004;Zhang et al, 2008), so it is unlikely that shifts in the fine aerosol size distribution are a dominant source of model error.…”
Section: Effect Of Relative Humiditymentioning
confidence: 99%
“…BBOA has a slightly smaller mode at ∼300 nm. Although BBOA is generated as primary aerosol from a combustion process, BBOA has a smaller fraction of ultrafine (d va < 100 nm) particles than OOA (McMeeking et al, 2005;Levin et al, 2010). In contrast, the size distribution of HOA is quite broad, with the largest fraction of ultrafine particles of any of these factors.…”
Section: Insights Into Ambient Aerosol and Ptof Samplingmentioning
confidence: 99%